Evaluating the Effect of Innovation Strategy on Customer Interest through the Memberku Application in Bakti Huria Syariah Cooperative - Nurul Uyun; Siti Fatimah; Kamaruddin Kamaruddin (Universitas Muhammadiyah Makassar, 2025)
This study explores the implementation of innovation strategies at Bakti Huria Syariah Makassar Cooperative and examines their impact on members’ interest in using the Memberku digital application. The research focuses on three core aspects: the application of innovation strategies in developing the Memberku application, the supporting and inhibiting factors influencing implementation, and the effectiveness of these strategies in encouraging members to adopt digital cooperative services. A qualitative descriptive approach was employed to gain in-depth insights into these processes. Data were collected through observation, semi-structured interviews, documentation, and a comprehensive literature review. The IT Division of the cooperative served as the primary data source, providing critical information regarding system updates, user growth, and operational challenges. Data analysis was conducted in three systematic stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the innovation strategy has been relatively effective in enhancing member engagement and promoting digital service adoption. Following a major system update in 2023, the cooperative recorded an increase of 300 new users, while the marketing team was tasked with acquiring at least ten additional users each month. Success was assessed through two key performance indicators: the number of active users and the volume of transactions through the application, both of which demonstrated significant growth. These results underscore the effectiveness of innovation strategies in driving the digital transformation of cooperative services.